2018
DOI: 10.1186/s12883-018-1144-y
|View full text |Cite
|
Sign up to set email alerts
|

A gaze-independent audiovisual brain-computer Interface for detecting awareness of patients with disorders of consciousness

Abstract: BackgroundCurrently, it is challenging to detect the awareness of patients who suffer disorders of consciousness (DOC). Brain-computer interfaces (BCIs), which do not depend on the behavioral response of patients, may serve for detecting the awareness in patients with DOC. However, we must develop effective BCIs for these patients because their ability to use BCIs does not as good as healthy users.MethodsBecause patients with DOC generally do not exhibit eye movements, a gaze-independent audiovisual BCI is put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…The affective modulation of the LPP is not influenced by the images' perceptual composition (Bradley, Hamby, Löw, & Lang, ; Codispoti, De Cesarei, & Ferrari, ; De Cesarei & Codispoti, ), exposure time (Codispoti et al, ), or repetition (Ferrari, Codispoti, & Bradley, ). These characteristics lead researchers to consider the LPP a robust index of motivational relevance (Lang & Bradley, ) and a useful tool for investigating affective processes in clinical populations, such as individuals affected by neurological disorders (Xie et al, ), post‐traumatic stress disorder (PTSD) and other anxiety disorders (Fitzgerald et al, ; MacNamara, Jackson, Fitzgerald, Hajcak, & Phan, ; Zhang et al, ), depression (Weinberg, Perlman, Kotov, & Hajcak, ), drug abuse (Dunning et al, ; Versace et al, ), anhedonia (Weinberg et al, ), psychopathy (Ellis, Schroder, Patrick, & Moser, ), and schizophrenia (Culbreth, Foti, Barch, Hajcak, & Kotov, ; Strandburg et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The affective modulation of the LPP is not influenced by the images' perceptual composition (Bradley, Hamby, Löw, & Lang, ; Codispoti, De Cesarei, & Ferrari, ; De Cesarei & Codispoti, ), exposure time (Codispoti et al, ), or repetition (Ferrari, Codispoti, & Bradley, ). These characteristics lead researchers to consider the LPP a robust index of motivational relevance (Lang & Bradley, ) and a useful tool for investigating affective processes in clinical populations, such as individuals affected by neurological disorders (Xie et al, ), post‐traumatic stress disorder (PTSD) and other anxiety disorders (Fitzgerald et al, ; MacNamara, Jackson, Fitzgerald, Hajcak, & Phan, ; Zhang et al, ), depression (Weinberg, Perlman, Kotov, & Hajcak, ), drug abuse (Dunning et al, ; Versace et al, ), anhedonia (Weinberg et al, ), psychopathy (Ellis, Schroder, Patrick, & Moser, ), and schizophrenia (Culbreth, Foti, Barch, Hajcak, & Kotov, ; Strandburg et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The third ERP component with a significant difference was between 700 and 780 ms in the frontal and central areas, and it might be a late positive component (LPC) related to the semantically congruent stimuli. Xie et al (2018) also observed an enhanced LPC amplitude induced by audiovisual stimuli compared with a unimodal stimulus in the semantically congruent condition at electrodes Fz, Cz, and Pz between 700 and 900 ms. The LPC component has been often observed in studies about semantics and in tasks such as memorizing congruous or incongruous auditory sentences (McCallum et al, 1984), memorizing word lists (Martin and Chao, 2001), and making decisions on congruency (Kounios and Holcomb, 1992).…”
Section: Discussionmentioning
confidence: 67%
“…As the N400 is primarily produced by incongruency, in the absence of a motor response, future research may wish to explore the N400 and incongruency-based paradigms as the foundation for gaze-independent audiovisual BCI systems (e.g., Xie et al, 2018). However, currently in the field of BCI, the N400 is largely discussed in the context of supporting improved outcomes for P300-based BCI devices, and N400 elicitation directly influences how the visual displays for gridbased P300 BCI devices are designed.…”
Section: Secondary Signal Related To Bci Controlmentioning
confidence: 99%